Grouting seepage characteristics in microfracture under triaxial stress conditions: Device design and experimental study - Shuai Zhang; Wei-Guo Qiao; Yue Wu; Feng Jiang; Hao Liu (Case Studies in Construction Materials, 2024)
Water plugging by grouting in rock microfracture is a technical challenge in deep underground engineering. In this paper, a novel grouting test system was developed, which can simulate microfracture grouting tests under triaxial stress conditions. A specimen preparation method that can monitor the seepage and diffusion of microfine cement slurry in microfracture was also proposed. Microfracture grouting model tests were conducted on sandstone-like specimens to investigate the effects of confining pressure, roughness, and microfracture aperture on the seepage and diffusion characteristics of sandstone-like specimens. The test results show that microfine cement slurry can effectively seal the microfracture. However, when the microfracture aperture is small or the roughness is large, the slurry is easy to gather and deposit at the inlet, resulting in the phenomenon of ''seepage filtration'', which makes it difficult for the slurry to be injected into the microfracture. The pressure at the measuring point gradually decreases along the seepage and diffusion direction of the slurry, and the decreasing trend increases with the increase of microfracture roughness. The nonlinear relationship between the slurry volume flow rate and the hydraulic gradient can be described by Forchheimer's law. Moreover, both coefficients a and b in Forchheimer's equation show a gradual increase with increasing microfracture roughness. This study can provide a meaningful reference for the development of rock microfracture grouting technology in deep engineering.